PENGEMBANGAN APLIKASI MOBILE MATH DIFFELEARN MATERI ARITMATIKA SOSIAL BERDASARKAN GAYA BELAJAR: Development Of Mobile Math Diffelearn Application For Social Arithmetic Material Based On Learning Style - Tri Yoga, Anggi; Bahrotul Ilmi, Noraniza (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
The existence of individuality challenges, student characteristics based on diverse learning styles, and differences in the level of student understanding in mathematics, more innovative media are needed. Learning media in the form of mobile applications plays a crucial role in enhancing the quality of mathematics learning, especially based on student learning styles. The aim of this research was to assess the development process, validity, and practicality of the Math DiffeLearn mobile application. The research method employed in this research is research and development using the ADDIE development model. The results of the study include: (a) the development process produces Math DiffeLearn mobile application products that can be applied to the learning process of grade VII junior high school mathematics, (b) the validity of the product is validated with a percentage of 76.25% by material expert 1, a percentage of 75% by material expert 2, and a percentage of 73.75% by media experts, (c) the practicality of the product is declared "very practical" or "very feasible" practicality with a percentage of 95% by practicing mathematics teachers and a percentage of 88.71% by students. In conclusion, the Math DiffeLearn mobile application has been tested valid and can be practically applied as a learning media on social arithmetic material for grade VII junior high school, especially based on student learning styles.